2015
DOI: 10.1038/bmt.2015.283
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal obstruction syndrome after allogeneic hematopoietic stem cell transplantation: Incidence, risk factors and outcomes

Abstract: This retrospective study was conducted in Japan to determine the incidence, risk factors and outcomes of sinusoidal obstruction syndrome (SOS) after allogeneic hematopoietic stem cell transplantation (HSCT). Among 4290 patients undergoing allogeneic HSCT between 1999 and 2010, 462 were diagnosed with SOS according to the Seattle criteria (cumulative incidence, 10.8%). The cumulative incidence of SOS diagnosed by the modified Seattle criteria was 9.3%. Of 462 patients, 107 met the Baltimore criteria and 168 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 37 publications
(55 reference statements)
4
61
1
Order By: Relevance
“…Studies that evaluated risk factors for VOD/SOS in large HSCT recipient populations over the past 5 to 7 years vary in consistency with previous data and reveal potential risk factors that have not previously been noted [21,23,26,[36][37][38][39] (Table 5). Among 10 such studies identified for this review, with total numbers ranging from 75 to 5072 patients, incidence of VOD/ SOS ranged from 2.0% (lowest incidence was diagnosed with EBMT criteria) to 30.7% (Table 5).…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 57%
See 3 more Smart Citations
“…Studies that evaluated risk factors for VOD/SOS in large HSCT recipient populations over the past 5 to 7 years vary in consistency with previous data and reveal potential risk factors that have not previously been noted [21,23,26,[36][37][38][39] (Table 5). Among 10 such studies identified for this review, with total numbers ranging from 75 to 5072 patients, incidence of VOD/ SOS ranged from 2.0% (lowest incidence was diagnosed with EBMT criteria) to 30.7% (Table 5).…”
Section: Recent Studies Of Risk Factors For Vod/sos In Hsct Recipientsmentioning
confidence: 57%
“…Identification of patients at highest risk for VOD/SOS may be key to prompt diagnosis and optimal management of VOD/ SOS [25]. Several analyses have shown an association between diagnosis using the modified Seattle criteria and better outcomes versus outcomes in patients diagnosed with the more stringent Baltimore criteria [23,26,27]. In a retrospective multicenter observational study of allogeneic HSCT recipients in Japan (n = 4290), VOD/SOS with MOD was associated with higher levels of total bilirubin, ascites, and encephalopathy at diagnosis, and patients who met the Baltimore criteria had lower rates of complete response to treatment (resolution of VOD/SOS and, if present, MOD) and overall survival compared with those who met the Seattle criteria alone in either the presence or absence of MOD (P < .001 for all comparisons) [26].…”
Section: Importance Of Vod/sos Risk Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Moreover, a large Japanese HSCT registry analysis of 4290 patients found a rate of severe VOD/SOS of 3.9%. 24 Although the difference between groups in day 1100 survival was statistically significant, day 1180 survival did not reach statistical significance. Importantly, all deaths in both groups after day 1100 were considered to be related to a cause other than VOD/SOS.…”
Section: 22mentioning
confidence: 92%